2002
DOI: 10.1038/sj.bjc.6600286
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HER-2/neu gene amplification and protein expression in non-small cell lung carcinomas

Abstract: HER-2/neu gene amplification and cell surface overexpression are important factors in breast cancer for prognosis and prediction of sensitivity to anti-HER-2/neu monoclonal antibody therapy. In lung cancer, the clinical significance of HER-2/neu expression is currently under evaluation. We investigated 238 non-small lung carcinomas for HER-2/neu protein overexpression by immunohistochemistry using the HercepTest. We found 2+ or 3+ overexpression in 39 patients (16%), including 35% in adenocarcinomas and 20% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
127
4
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(149 citation statements)
references
References 25 publications
10
127
4
8
Order By: Relevance
“…The frequency observed in our study is in the range (1-5%) of other studies performing ERBB2 FISH in lung cancer. 11,13,15,16 The predilection of adenocarcinomas for ERBB2 amplification is in line with the results from earlier studies showing a correlation of HER2 expression with this histologic subtype. 11 We did not observe significant associations with tumor stage or presence of metastases but found a significant link between ERBB2 amplification and poor prognosis although in univariate analysis only.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The frequency observed in our study is in the range (1-5%) of other studies performing ERBB2 FISH in lung cancer. 11,13,15,16 The predilection of adenocarcinomas for ERBB2 amplification is in line with the results from earlier studies showing a correlation of HER2 expression with this histologic subtype. 11 We did not observe significant associations with tumor stage or presence of metastases but found a significant link between ERBB2 amplification and poor prognosis although in univariate analysis only.…”
Section: Discussionsupporting
confidence: 89%
“…9 HER2 overexpression in adenocarcinoma and squamous cell carcinoma of the lung as assessed by immunohistochemistry is found in 2.5-43% of cases with a clear tendency toward higher rates of positivity in adenocarcinoma than in squamous cell carcinoma. [10][11][12][13] Studies assessing ERBB2 amplification found a similar variability but usually with a much lower frequency of amplified tumors. The different analytical methods such as PCR, Southern blot or fluorescence in-situ hybridization (FISH) used and the varying definitions of amplification have resulted in a wide range (1-23%) of cases reported to be amplified.…”
mentioning
confidence: 86%
“…The inconvenience of ELISA is the requirement of fresh or frozen tissue and calculation of an average c-erbB-2 content of tumour and normal tissue, but the availability for measuring the circulating levels of this protein is an interesting opportunity to assess its overexpression in patients with tumours that are not easily accessible for biopsy. Finally, Hirsch et al (2002) found a good correlation between the IHC and FISH results in twothirds of the 51 tumours investigated. Demonstration of HER-2/neu overexpression in NSCLC using a standardised method is essential for establishing clinical trials for anti-HER-2 drugs.…”
Section: Discussionmentioning
confidence: 71%
“…A total of 39 studies, published between 1990 and 2002, were found eligible (Kern et al, 1990(Kern et al, , 1994Tateishi et al, 1991Tateishi et al, , 1994Volm et al, 1992Volm et al, , 1993aHarpole et al, 1995aHarpole et al, , b, 1996Giatromanolaki et al, 1996a, b;Pfeiffer et al, 1996;Koukouraki et al, 1997Koukouraki et al, , 2000MacKinnon et al, 1997;Pastorino et al, 1997;Visscher et al, 1997;Yu et al, 1997;Graziano et al, 1998;Greatens et al, 1998;Hsieh et al, 1998;Kim et al, 1998;Kwiatkowski et al, 1998;Nemunaitis et al, 1998;Cantero et al, 1999Cantero et al, , 2000D'Amico et al, 1999;Fu et al, 1999;Moldvay et al, 2000;Schneider et al, 2000;Ardizzoni et al, 2001;Brabender et al, 2001;Liao et al, 2001;Shou et al, 2001;Carbognani et al, 2002;Han et al, 2002;Hirsch et al, 2002;Potti et al, 2002;Selvaggi et al, 2002). Nine of the articles were excluded because identical cohorts of patients were used (studies that were excluded and included were, respectively, references (Cantero et al, 1999) and (Cantero et al, 2000), (Giatromanolaki et al, 1996b;…”
Section: Studies Selection and Characteristicsmentioning
confidence: 99%
“…However, genetic gains of chromosome 17q have also been reported in lung adenocarcinomas but the nature of the genes concerned by this genetic alteration remains poorly investigated (Balsara and Testa, 2002). ERBB2 is expressed in about 30% of Non-Small Cell Lung Carcinomas (NSCLC), especially adenocarcinomas, although gene amplification is not usually the underlying mechanism (Hirsch et al, 2002). In our analysis, TRAF4 overexpression was most commonly detected in this cancer type with 60% of lung adenocarcinomas concerned and it is due to gene amplification in about 38% of the cases.…”
mentioning
confidence: 99%